2022
DOI: 10.1186/s12891-022-05126-x
|View full text |Cite
|
Sign up to set email alerts
|

Musculoskeletal care – at the confluence of data science, sensors, engineering, and computation

Abstract: Data has always been integral to modern medicine in almost all aspects of patient care and the recent proliferation of data has opened up innumerable opportunities for all the stakeholders in trying to improve the quality of care and health outcomes including quality of life and rehabilitation. Greater usage and adoption of digital technologies have led to the convergence of health data in different forms – clinical, self-reported, electronic health records social media, etc. The application and utilization of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 37 publications
0
6
0
Order By: Relevance
“…This allowed us to examine and show in this article the whole spectrum of possible solutions within the investigated area. These different chainmail versions we used in the author's hand exoskeleton described in other publications [40,41].…”
Section: Methodsmentioning
confidence: 99%
“…This allowed us to examine and show in this article the whole spectrum of possible solutions within the investigated area. These different chainmail versions we used in the author's hand exoskeleton described in other publications [40,41].…”
Section: Methodsmentioning
confidence: 99%
“…We can, therefore, conclude that there are relatively few publications on exoskeletons. This factor highlights the need to intensify research and increase the number of scientific publications, especially since the above-mentioned 20 publications included three reviews [20][21][22] and two clinical trials [23,24] but no meta-analyses. In the case of 3D-printed orthoses, only four reviews and nine clinical trials were identified, with no meta-analyses.…”
Section: Exoskeletons As 3d-printed Medical Devicesmentioning
confidence: 99%
“…Exoskeletons, 3D printing, and virtual rehabilitation all promise to provide patients with precise, low-cost interventions, but they are still in the early stages of development. Modern simulators, tools, and systems are now part of physical rehabilitation technologies, such as microprocessor-based and computerassisted equipment with real-time monitoring [16]. Robotic rehabilitation devices are gaining popularity in dealing with injuries to the limbs.…”
Section: Introductionmentioning
confidence: 99%